Pengaruh Faktor Fundamental Terhadap Harga Saham Pada Perusahaan Subsektor Farmasi Yang Terdaftar Di Bursa Efek Indonesia - Nadi Hernadi Moorcy; Shinta Nuriah Syahad; Juwari Juwari (CV. Ulil Albab Corp, 2026)
This study aims to analyze the effect of Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Equity (ROE) on stock prices in pharmaceutical subsector companies listed on the Indonesia Stock Exchange (IDX) during the 2020 - 2024 period. This research employs a quantitative approach using secondary data obtained from published financial statements. The sample was determined using purposive sampling based on predetermined criteria. Data analysis was conducted using multiple linear regression with the assistance of statistical software. The results show that partially Current Ratio (CR) has a negative and significant effect on stock prices, indicating that higher liquidity is not always positively perceived by investors. Debt to Equity Ratio (DER) has a negative and significant effect on stock prices, suggesting that higher levels of debt increase financial risk and reduce investor interest. Meanwhile, Return on Equity (ROE) has a positive but not significant effect on stock prices, indicating that profitability is not the primary factor considered by investors in making investment decisions.